EFEK PROTEKTIF VITAMIN E DAN SELENIUM TERHADAP KADAR KOLESTEROL DARAH PADA PENDERITA PENYAKIT JANTUNG - Diana, Widia Pebri (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Cardiovascular disease (CVD) is a disease which disturbing the cardiovascular system. CVD is a disesase that can be prevented; 50 % of death can be prevented by changing the food habit. The aim is to know relationship of vitamine E and celenium with total cholesterol concentration in CVD patient in RSUD dr. M. Yunus Bengkulu 2013. Research design is cross sectional. Data are analysed by univariat and bivariat analysis, correlation test. The sample are 35 people. The results of this research show that meaningfull relationship between vitamine E intake and total cholesterol consentration (p = 0.02), and celenium intake with total cholesterol consentration (p = 0.037) on CVD patient.